Rancang Bangun Sistem Informasi Bimbingan Online (SIMABIN) dengan Fitur Whatsapp Gateway Notifications - Iin Iin; Ali Ikbal; Krisna Mulyana; Siti Saropah (Masoem University, 2022)
The Academic Manager of STMIK IKMI Cirebon does not know the status of theses and final assignments submitted by students for the 2020/2021 academic year. They do not know who has or has not completed the mentoring procedure until a mentoring report is issued at the end of the mentoring period. The process is done offline and each process involves manual labor, paper-based guidance cards, duplicate, invalid, or empty data are examples of data restrictions. It can take a while to search for data, missing files, or missing files through physically stacked folders. An integrated web-based information system is the solution. Users can access it from any platform, including supervisors, BAAK, heads of study programs, and students. The research method using UML (Unified Modeling Language) and Extreme Programming (XP). The results showed that White Box Testing was 85% in the Online Guidance Information System (SIMABIN) for the main module so it was feasible for the deployment process. The application has gone through the deployment process and can record all student guidance activities starting from the process of submitting titles, guidance requirements, assignment of supervisors, process of guidance sessions, to the eligibility of hearings for each guidance week. The application can be accessed at https://ikmiapp.web.id/simabin.